2020
DOI: 10.3389/fmicb.2020.01251
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein Subunit Gαi in Mitochondria, MrGPA1, Affects Conidiation, Stress Resistance, and Virulence of Entomopathogenic Fungus Metarhizium robertsii

Abstract: G proteins are critical modulators or transducers in various transmembrane signaling systems. They play key roles in numerous biological processes in fungi, including vegetative growth, development of infection-related structures, asexual conidiation, and virulence. However, functions of G proteins in entomopathogenic fungi remain unclear. Here, we characterized the roles of MrGPA1, a G-protein subunit Gα i , in conidiation, stress resistance, and virulence in Metarhizium robertsii. MrGPA1 was localized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 67 publications
3
22
1
Order By: Relevance
“…surface hydrophobin Mpg1 or a transmembrane protein Pth11 leads to a defect in contact-induced appressorium formation. The surface-induced appressorium defect in all two deletion mutants can be bypassed by the addition of cAMP (Liu and Dean, 1997). These results indirectly verified the role of the cAMP-PKA pathway on the infection structure formation in FIGURE 6 | Effect of AaPKAc on the pathogenicity of A. alternata.…”
Section: Discussionsupporting
confidence: 57%
“…surface hydrophobin Mpg1 or a transmembrane protein Pth11 leads to a defect in contact-induced appressorium formation. The surface-induced appressorium defect in all two deletion mutants can be bypassed by the addition of cAMP (Liu and Dean, 1997). These results indirectly verified the role of the cAMP-PKA pathway on the infection structure formation in FIGURE 6 | Effect of AaPKAc on the pathogenicity of A. alternata.…”
Section: Discussionsupporting
confidence: 57%
“…Both the Gα-GTP and Gβγ heterocomplexes can transmit signals to downstream effectors, including cAMP-dependent protein kinase A (PKA), ion channels, and mitogen-activated protein kinases [ 1 , 3 ]. In fungi, G proteins are associated with numerous biological processes, including sexual and asexual reproduction, virulence, and response to external signal stimuli [ 1 , 4 , 5 ]. For example, GpaB (Gα) regulates growth and asexual development via the cAMP/PKA signal transduction pathway in Aspergillus fumigatus [ 6 ], whereas SfaD (Gβ) and GpgA (Gγ) regulate trehalose hydrolysis, conidial germination, hyphal growth, and gliotoxin biosynthesis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Gα and Gβγ activate downstream effectors, including adenylyl cyclases, mitogen-activated protein kinases (MAPK)s, ion channels, phosphodiesterases, and phospholipases [14][15][16][17]. Previous studies have shown that Gα subunits are involved in the regulation of various physiological processes of fungi [18][19][20]. In Metarhizium robertsii, MrGpa1 deletion caused reductions in the number of conidia formed, germination, stress sensitivity, and pathogenicity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Gα subunits are involved in the regulation of various physiological processes of fungi [18][19][20]. In Metarhizium robertsii, MrGpa1 deletion caused reductions in the number of conidia formed, germination, stress sensitivity, and pathogenicity [18]. In Aspergillus fumigatus, three Gα subunits were found and shown to participate in regulation of hyphae growth, asexual development, germination, oxidative stress tolerance, and gliotoxin production [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation